Structural, Magnetic, and Optical Studies of Ni–Mg Ferrites Synthesized by Polyol Method. Issue 22 (20th October 2021) - Dhanyaprabha, KrishnaPillai Chandrikamma; Jacob, Bibin; Mohan, Manoj; Al-Omari, Imaddin A.; Al-Harthi, Salim H.; Myint, Myo T.Z.; Thomas, Hysen
Abstract : Magnesium and nickel‐substituted ferrites belong to an important class of spinel ferrites with wide variety of applications. Herein, preparation and characterization of pure, single‐phase Ni–Mg ferrites using a cost‐effective method, which yield high‐quality nanosized particles with good chemical homogeneity, are reported. A series of Ni x Mg(1− x ) Fe2 O4 nanocrystalline powders ( x  = 1, 0.75, 0.5, 0.25, 0) is prepared using polyol method and a detailed investigation on the effect of dopant substitution on microstructural magnetic as well as optical properties is conducted. The as‐prepared samples are subsequently characterized using X‐ray diffractometer (XRD), X‐ray photoelectron spectroscopy (XPS), Fourier‐transform infrared spectroscopy (FTIR), Field‐emission scanning electron microscope (FESEM), Brunauer, Emmett, and Teller (BET), Mossbauer spectroscopy, Vibrating sample magnetometer (VSM), and UV–visible diffuse reflectance spectroscopy. Rietveld refinement confirms the single‐phase cubic structure with Fd‐3m (227) space group of Ni x Mg(1− x ) Fe2 O4 series. The cation distribution can be represented as [Mg(1− x − y ) Fe( δ ) ] A [Mg( x ) Ni( y ) Fe(2− δ ) ] B O4 . FTIR bands at the finger print region of ferrites and Mossbauer analysis confirms the proposed cation distribution from Rietveld refinement. The magnetic nature is confirmed from Mossbauer and VSM analysis. In VSM, the saturation magnetization of the samples exhibits an increasing trend with nickel substitution. The optical studies of the series Ni x Mg(1− x ) Fe2 O4 are conducted by UV–visible diffuse reflectance spectroscopy. Abstract : Ni–Mg ferrites are synthesized by polyol method. The effect of dopants is studied in detail. The samples are characterized using X‐ray diffractometer, X‐ray photoelectron spectroscopy, field‐emission scanning electron microscope, Brunauer, Emmett, and Teller, Fourier‐transform infrared spectroscopy, Mossbauer, vibrating sample magnetometer, and UV–vis diffuse reflectance spectroscopy. The samples show increased magnetic and optical properties as Ni 2+ increases.